Glasbene didaktične igre in glasbeno-razvojni dosežki prvošolcev - Kopačin, Barbara (Revija za elementarno izobraževanje, 2020)
Didactic Musical Games and Music Development Achievements of Year One pupils. Our research interest was to determine how regular use of didactic musical games during the other school lessons influences the development of music skills and performance during the music lessons. The study sample included 71 year one children of the selected elementary school who conducted music didactic games in various subjects for four months. At the beginning and at the end of the four months period the children carried out specially developed 13 music tasks to determine their level of knowledge in various music skills. The children of the experimental group achieved better results on the tests than those of the control group in all measured categories.